Triple Positivity for Anti–Citrullinated Protein Autoantibodies, Rheumatoid Factor, and Anti–Carbamylated Protein Antibodies Conferring High Specificity for Rheumatoid Arthritis: Implications for Very Early Identification of At‐Risk Individuals. Issue 11 (16th September 2018) - Verheul, Marije K.; Böhringer, Stefan; van Delft, Myrthe A. M.; Jones, Jonathan D.; Rigby, William F. C.; Gan, Ryan W.; Holers, V. Michael; Edison, Jess D.; Deane, Kevin D.; Janssen, Koen M. J.; Westra, Johanna; Brink, Mikael; et al.
Abstract : Objective: In rheumatoid arthritis (RA), anti–citrullinated protein antibodies (ACPAs) and rheumatoid factor (RF) are commonly used to aid in the diagnosis. Although these autoantibodies are mainly found in RA, their specificity is not optimal. It is therefore difficult to identify RA patients, especially in very early disease, based on the presence of ACPAs and RF alone. In addition, anti–carbamylated protein (anti‐CarP) antibodies have diagnostic and prognostic value, since their presence is associated with joint damage in RA patients and also associated with the future development of RA in patients with arthralgia. Therefore, the aim of the present study was to investigate the value of combined antibody testing in relation to prediction and diagnosis of (early) RA. Methods: A literature search resulted in identification of 12 relevant studies, consisting of RA patients, pre‐RA individuals, disease controls, healthy first‐degree relatives of RA patients, and healthy control subjects, in which data on RF, ACPAs, and anti‐CarP antibody status were available. Using these data, random effects meta‐analyses were carried out for several antibody combinations. Results: The individual antibodies were highly prevalent in patients with RA (34–80%) compared to the control groups, but were also present in non‐RA controls (0–23%). For the classification of most subjects correctly as having RA or as a non‐RA control, the combination of ACPAs and/or RF often performed well (specificity 65–100%, sensitivity 59–88%). However, triple positivity for ACPAs, RF, and anti‐CarP antibodies resulted in a higher specificity for RA (98–100%), accompanied by a lower sensitivity (11–39%). Conclusion: As the rheumatology field is moving toward very early identification of RA and possible screening for individuals at maximum risk of RA in populations with a low pretest probability, an autoantibody profile of triple positivity for ACPAs, RF, and anti‐CarP provides interesting information that might help identify individuals at risk of developing RA.